If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(5x + -7y + -9x) = 0 Reorder the terms: -3(5x + -9x + -7y) = 0 Combine like terms: 5x + -9x = -4x -3(-4x + -7y) = 0 (-4x * -3 + -7y * -3) = 0 (12x + 21y) = 0 Solving 12x + 21y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-21y' to each side of the equation. 12x + 21y + -21y = 0 + -21y Combine like terms: 21y + -21y = 0 12x + 0 = 0 + -21y 12x = 0 + -21y Remove the zero: 12x = -21y Divide each side by '12'. x = -1.75y Simplifying x = -1.75y
| 206=60-x | | x+3-2=-5 | | 500x+(349.5-50x)=2370 | | 2x+x+108=180 | | 1(8-x)=8-x | | xx/5-7=-8 | | 5+k-3=3 | | 1x(8-x)=8-x | | 205-v=158 | | M-48=87 | | X-50=-25 | | 20x+45=225 | | 1l(8-x)=8-x | | 6w+8=48 | | q/3=31/1 | | 74=28+V | | 4j/12=-1 | | 72-w=8w | | y=rx+3 | | 13b=78 | | X-4=-9-4x | | 5n-2-7n=-14 | | 4x-18=3(2x-9) | | 7-2n=-13-6n | | 7.50p+2.50=12.50 | | 8x+3+4(x-5)= | | 5(r-5)-4(r-1)=2(r+4) | | 2M/(22M^2) | | 3x-2(4x-3)=6-(x+8) | | -7y+3=-22 | | y+2*-4=-6 | | 8w=27+5w |